Проблемное поле экзистенциальной социологии - Мельников, А. (Социология: теория, методы, маркетинг, 2008)
Analyzing the problem field of existential sociology, the paper discusses two main versions of existential sociology presented in works by Edward Tiryakian and by sociologists of the Californian school (Douglas school). Regarding both versions, as well as conceptions of the other existential thinkers, the author distinguishes funda mental problems in an existential approach of sociology and briefly analyzes each of them. Moreover, the structure of existential sociology is represented, its micro- and macrolevels and their interdependence are examined. The main theoretical and metho dological problems of this branch of sociology are highlighted, as well as some developmental prospects are suggested.